Chemical and phytochemical investigation on Catharantus roseus (L.) G. Don - Castillo, Clarissa G.; Santos, Rizalina B.; Concepcion. Adoracion B. (Quezon City: Department of Pharmaceutical Chemistry, College of Pharmacy, University of the Philippines, 1981.)
Catharantus roseus (L.) G. Don belonging to the plant family Apocynaceae grows abundantly throughout the Philippines. The recent discovery of the oncolytic alkaloids from this plant represented a new class of anti-tumor agents and has been of considerable interest to study. A number of other chemically inactive alkaloids which are also present, prompted us to determine more about its plant constituents, with special emphasis being laid upon the alkaloidal contents in the leaves. Chemical and phytochemical tests will be employed such as organoleptic test, qualitative chemical test using test reagents, extraction processes, TLC and melting point determination.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1981.
Keywords: Catharanthus; Periwinkle